2001
DOI: 10.1212/wnl.56.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Classification criteria for mild cognitive impairment

Abstract: Article abstract-Objective: To evaluate the predictive validity and temporal stability of diagnostic criteria for mild cognitive impairment (MCI). Background: MCI has been proposed as a nosologic entity referring to elderly persons with subclinical cognitive deficits due to incipient dementia. Classification criteria, which have been derived from small, selected clinical groups, are currently disputed, and have not yet been assessed within the general population. Methods: Subjects meeting current criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

40
606
9
47

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 776 publications
(705 citation statements)
references
References 18 publications
40
606
9
47
Order By: Relevance
“…It is likely that about 30% of these subjects will have dementia within another 3 years. 40 We selected subjects with no obvious cognitive impairment at baseline from a large longitudinal population-based study; follow-up measurements were obtained at 3 and 6 years. We assessed cognition by measures sensitive to cognitive decline.…”
Section: Figure Six-year Change In Cognitive Test Scores According Tmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that about 30% of these subjects will have dementia within another 3 years. 40 We selected subjects with no obvious cognitive impairment at baseline from a large longitudinal population-based study; follow-up measurements were obtained at 3 and 6 years. We assessed cognition by measures sensitive to cognitive decline.…”
Section: Figure Six-year Change In Cognitive Test Scores According Tmentioning
confidence: 99%
“…In addition, we combined these measures to study the rates of subjects who had AACD, which has been shown to be predictive for dementia in the population. 40 Furthermore, we assessed memory problems with one simple question that appeared to be a sensitive predictor of objective cognitive decline in cognitively normal elderly persons. 8 If symptoms of dementia already exist, the caregiver's report on memory problems seems to be more reliable for diagnosing dementia than does the subject's report.…”
Section: Figure Six-year Change In Cognitive Test Scores According Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that predict dementia onset within specific time periods are used to identify high risk groups. The most widely used approach is to identify individuals with memory impairment who do not meet criteria for dementia (Albert et al, 2001;Larrieu et al, 2002;Petersen, 2004;Ritchie et al, 2001). A subgroup of these individuals meeting criteria for amnestic Mild Cognitive Impairment (aMCI) develop AD at elevated rates and have become the targets of secondary prevention trials (Petersen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…BADLs are highly correlated with motor functioning and coordination (Bennett et al, 2002;Boyle et al, 2002;Cahn et al, 1998). In contrast, declines in IADLs have been shown to be influenced by cognitive functioning, are affected relatively early in the course of dementia (Stern et al, 1990), and may be present in preclinical dementia states such as mild cognitive impairment (MCI; Griffith et al, 2003;Ritchie et al, 2001). Assessment of ADLs in large-scale studies is usually conducted through informant report.…”
Section: Introductionmentioning
confidence: 99%